Evaluation Of Anti-Fungal Potential Of Cinnamomum Zeylanicum Blume (Lauraceae) Barks Extract For Onychomycosis - S, Manivannan; S, Bhuvaneswari (Kongunadu Research Journal, 2019)
Onychomycosis is a fungal infection of nails caused by dermatophytes, yeasts of nondermatophyte molds. Far more than being a simple cosmetic problem, infected nail serves as a chronic reservoir, which can give rise to repeated mycotic infections and represents about 30% of mycotic cutaneous infections. The prevalence rate of onychomycosis is determined by age, predisposing factor, social class, occupation, climate,living environment. To evaluation of Anti-fungal potential of Cinnamomum Zeylanicum Blume (Lauraceae) Barks Extract for Onychomycosis. The C. Zeylanicum barks crude extracts were obtained by soxhlet-solidliquid extraction using ethanol and aqueous. The dermatophytes namely, Trichophyton rubrum, Trichophyton mentagrophytes, Trichophyton simii, Epidermophyton floccosum and Candida albicans were recovered from rice farmers in Orathanadu, Thanjavur (Dt), Tamil Nadu. The antifungal activity, minimum inhibitory concentrations and minimum fungicidal concentrations against the onychomycosis of C. zeylanicum was determined by the disc diffusion methods in sabouraud dextrose agar using ketoconazole (2mg/disc) as a positive control. Phytochemical analysis revealed the presence of wide range of bioactive constituents like flavonoids, tannins, alkaloids, saponins, terpenes and steroids. The ethanol barks extract inhibited all test organisms at the minimum concentration of 25 mg/ml while fungicidal actions were observed at a concentration of 50 mg/ml for T. rubrum, 180 mg/ml for T. mentagrophytes, 160 mg/ml for T. simii, 120 mg/ml for E. floccosum and 60 mg/ml for C. albicans. The ability of the extracts to inhibit the growth of fungi likes dermatophytes and yeast is an indication of the antifungal potential of C. zylanicum, which makes the candidate for production of antifungal agents.